Do bilateral power deficits influence direction-specific movement patterns? - Hoffman, J. R.; Ratamess, N. A.; Klatt, M.; Faigenbaum, A. D.; Kang, J. (Research in Sports Medicine, 2007)
This study examined the effect of bilateral power differences on direction-specific movement patterns in American collegiate football players. Sixty-two college football players performed unilateral vertical jump testing prior to agility testing (3-cone drill). Three trials were performed on the subjects' dominant and nondominant sides. A significant difference (9.7 ± 6.9%) in unilateral jump power was observed between dominant and nondominant legs. No difference (p > 0.05) was seen, however, in agility performance between dominant (8.02 ± 0.51 s) and nondominant (7.97 ± 0.51 s) sides. Unilateral power in the nondominant leg had a low-to-moderate, correlation-to-agility sprint times performed on the subject's dominant (r = -0.36, p < 0.05) and nondominant (r = -0.37, p < 0.05) sides. Although power performance in the nondominant leg appears to correlate to agility performance, bilateral power deficits do not appear to relate to performance differences during direction-specific agility tests.